Analysis and Prediction of Heat Induced Deformation Produced By the Line Heating Process Using the Finite Element Method - Vega, Adán (Universidad Tecnológica de Panamá, Panamá, 2009)
To get an insight into the relationship between heating conditions and inherent deformation, the key to automate the plate forming by line heating, a series of experiments and/or numerical analyses is required. To replace costly experimental work, the finite element method (FEM), which is considered the most effective tool, is used in analysis. Two different analyses are required, namely heat conduction and thermal-elastic-plastic deformation analyses. In both of them a mesh model is need. In order to choose the most appropriate mesh model, the relationship between degree of freedom (DOF) and the computational time plays a key role. It is a fact that the usage of small element in the heating area increases the accuracy of the predictive model increasing the DOF. As is well known, a large number of DOF may result in an unrealistic computing time even if faster computer are used. Therefore, it is necessary to find the most appropriate mesh model that can be used to simulate different plate size under acceptable time. In this paper, a study on the best practices for analysis and prediction of the inherent deformation produced by line heating is first given. Then to a procedure that can be used to select the most appropriate mesh model for analysis of the line heating process is presented. The discussion includes: the influence of the model size, the number of elements through the thickness and the size of the elements. The analysis also considers the case of multiple heating lines. Finally, recommendations about selection of mesh model are presented.